Penggunaan Sensor Piezoelektrik sebagai Pad Trigger Rebana Untuk Menunjang Dinamika Ketukan - Syahida Muâ€™aliman; Ulfah Mediaty Arief; Eko Supraptono (Emitor: Jurnal Teknik Elektro, 2023)
Rebana is valuable cultural heritage and contain religious values. Along with the development of technology, a new innovation emerged in rebana, namely playing tambourines using drum pad triggers. The use of drum Pad Trigger in tambourine games makes it easier for tambourine players. This study aims to (1) design and make a trigger pad, (2) produce a tambourine Pad Trigger using a Piezoelectric sensor so as to produce tambourine beat dynamics, and (3) find out the test results of the Piezoelectric sensor to reduce noise. Method: The research method used is a research and development model. The steps that will be taken are to make observations about the use of Piezoelectric sensors on a drum and bonang musical instrument which is tested to be applied to tambourine musical instruments. In the process, researchers combined several inputs from similar previous studies to be developed into a tambourine Pad Trigger product to be useful for its target. This research will result in findings related to the use of Piezoelectric sensors in tambourine innovations; Knowing the results of quality testing of tambourine tool development. Conclusion: The results proved that the Piezoelectric sensor on the tambourine Trigger Pad uses Arduino nano as a microcontroller and microSD adapter as a storage of sound samples worth playing like the use of conventional tambourines and can produce the same sound as the original tambourine.Â  The use of Piezoelectric sensors on the tambourine Trigger Pad can reduce noise from outside. Piezoelectric sensors can also bring out dynamics in tambourine games evidenced by good output values in the microcontroller.